Papua New Guinea : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that Papua New Guinea's economy is experiencing an important transition, as new liquefied natural gas (LNG) production and exports commence. With LNG production and exports now starting, resource sector growth is projected to surge in 2015, but spillovers to the rest of the economy may be more limited. Inflation has moderated from its peaks during the construction boom and is likely to remain reasonably low given the global outlook for commodity prices. The ongoing economic transition calls for adjustment of macroeconomic policies to safeguard macrofinancial stability.